UNVEILING THE THYROID- PROSTATE NEXUS: A STUDY ON THYROID FUNCTION IN PROSTATE CANCER PATIENTS IN KHARTOUM STATE - Abdallah, Amina M.; Elhassan , Omar S.; Hamad, Malik A. (Research Journal of Health, Medicine and Nursing, 2024)
Prostate cancer, characterized by uncontrolled tumor growth resulting from imbalances in cell division and death rates, remains a significant health concern globally. This study explores the intricate interplay between thyroid hormones, specifically triiodothyronine (T3) and thyroxine (T4), and prostate cancer development and progression. Adenocarcinomas, the predominant form of prostate cancers, often undergo mutations, including those in retinoblastoma genes, further exacerbating tumor progression and metastasis. The hypothesized role of T3 and T4 in promoting carcinogenesis is rooted in their vital functions in cell differentiation, growth, metabolism, and their influence on tumor-induced angiogenesis. In vitro studies have demonstrated the ability of these hormones to enhance prostate cancer cell proliferation. This research investigates the association between thyroid status, characterized by thyroid-stimulating hormone (TSH), T4, and T3 levels, and prostate cancer risk. The study posits that hypothyroid men may experience a reduced risk of prostate cancer, while hyperthyroid men may face an increased risk. Recognizing the limitations of prostate-specific antigen (PSA) as a biomarker for prostate cancer, the study emphasizes the need for a nuanced understanding of serum PSA levels to avoid unnecessary biopsy procedures. PSA, although widely used for screening and monitoring treatment response, often yields false positives, prompting unnecessary interventions. The study seeks to shed light on the complex relationship between thyroid function and prostate cancer risk, offering insights that could refine risk assessment and early detection strategies. In addition to reviewing existing literature, this research evaluates the link between serum T3 levels and the risk of recurrence in patients treated for localized prostate cancer. The study aims to contribute valuable knowledge to the field, guiding future research and potentially informing clinical practices for more precise prostate cancer risk assessment.